Effects of prior heavy exercise on energy supply and 4000-m cycling performance - Palmer, C. D.; Jones, A. W.; Kennedy, G. J.; Cotter, J. D. (Medicine & Science in Sports & Exercise, 2009)
Purpose: This study was designed to determine the effects of prior exercise on energy supply and performance in a laboratory-based 4000-m time trial.